Projeto de um sistema experimental para monitoramento da sedimentação de partículas em suspensões aquosas submetidas a gradientes de temperaturas - Alves, Ana Gabriela Bueno (2024)
Due to Brazil’s increasing demand for fossil fuels, the high productivity of companies in this sector has become increasingly crucial. Petrobras, as a prominent example, has found ways to enhance the efficiency of its production and, to this end, has intensified exploration in ultra-deep wells, resulting in a substantial increase in its daily production. However, when drilling in such deep regions, it is important to consider that the process will be exposed to high temperatures and pressures. During the drilling phase, a fluid with various functions is used, and this fluid has characteristics that are sensitive to elevated temperatures, requiring constant experimentation to develop formulations capable of withstanding these extreme conditions. Therefore, understanding the behavior of these fluids when exposed to intense temperatures is of utmost importance. Accordingly, this study used the gamma-ray attenuation technique to monitor the behavior of the volumetric concentration of solids in aqueous suspensions exposed to high temperatures and thermal gradients. To make this possible, it was necessary to construct equipment that would allow monitoring through the mentioned technique and exposure of the sedimentation area to a thermal gradient. Consequently, dynamic and static tests were conducted. The dynamic test was designed to analyze the influence of temperature on sedimentation time. Thus, monitoring was carried out during the sedimentation phenomenon in heated suspensions. The compaction test was proposed to analyze the influence of temperature on the compaction of solids, with monitoring performed on heated suspensions and after sediment stabilization. The thermal gradient test was proposed to analyze the influence of a temperature gradient on the compaction of solids. For this, the sedimentation area was exposed to a hot wall, and the solids compacted under the influence of a temperature gradient, with monitoring done after the sediment stabilization. In all tests, the suspensions were composed of water and calcium carbonate. The results revealed that temperature influences the sedimentation rate of the studied fluid, as hotter suspensions resulted in shorter sedimentation times. Additionally, temperature influenced the compaction of solids, both when the fluid was fully heated and when subjected to a thermal gradient, as hotter regions resulted in more expanded sediments. Therefore, the study will contribute to advancing the understanding of the behavior of fluids with characteristics similar to drilling fluid and provide a better understanding of the solid-liquid separation phenomenon in heated suspensions.